Cloning and characterization of the Saccharomyces cerevisiae CDC6 gene. - Lisziewicz, J (1988)
The yeast cell division cycle gene CDC6 was isolated by complementation of a temperature-sensitive cdc6 mutant with a genomic library. The amino acid sequence of the 48 kDalton CDC6 gene product, as deduced from DNA sequence data, includes the three consensus peptide motifs involved in guanine nucleotide binding and GTPase activity, a target site for cAMP-dependent protein kinase and a carboxy-terminal domain related to metallothionein sequences. A plasmid-encoded CDC6-beta-galactosidase hybrid protein was located at the plasma membrane by indirect immunofluorescence. Disruption experiments indicate that the CDC6 gene product is essential for mitotic growth.